The Application Of Educational Management Principles In The Management Of Inclusive School Curricula - Marilin Kristina; Tri Yuni Hendrowati; Dewi Ratnaningsih (Mathematics Education Study Program, 2025)
Inclusive education is a critical component of contemporary educational reforms, emphasizing equitable access and quality learning for all students, including those with special needs. This study explores applying educational management principles in curricula management within inclusive schools in Indonesia. The research uses a qualitative approach to examine the planning, implementation, and evaluation processes involved in inclusive curriculum management. Key findings indicate that effective curriculum management involves systematic planning, teacher capacity building, and stakeholder collaboration, addressing barriers such as limited resources and insufficient training. The results study highlight the importance of adaptable strategies and participatory management to enhance the inclusivity of educational practices. These insights contribute to the development of policies and practices that support equitable and sustainable inclusive education